STUDI EKSPERIMENTAL TENTANG PENGARUH VARIASI RAPAT ARUS PADA HARD CHROME ELECTROPLATING TERHADAP KARAKTERISTIK PERMUKAAN BAJA KARBON RENDAH - Harnowo Supriadi (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Lampung, 2010)
The objective of the research is to investigate the effect of hard chrome electroplating on low carbon steel surface characteristic. This experimental research used low carbon steel as material that has been coated by hard chrome electroplating, chromium powder, and Pb alloy as cathode. The instrument for the research were rectifier, hardness testing machine LECO M-400-H1, optical microscope and digital camera. This research had been performed by making variation of current ((15 A/dm2, 30 A/dm2, 45 A/dm2 and 60 A/dm2).The result of this research shows that the maximum hardness of low carbon steel after coated by hard chrome electroplating was 576,50 VHN, when hard chrome electroplating had been performed on current 45 A/dm2. Beside that, on the same current (45 A/dm2) also gained maximum chrome layer (38,65 µm).Keywords: low carbon steel, hard chrome electroplating, hardness, deep of coated.